A Middleware Approach to Integrate Referent Tracking in EHR Systems. - MANZOOR, Shahid (American Medical Informatics Association, 2007)
The purpose of a Referent Tracking System (RTS) is to manage the representation of particulars in a database and to share this information with Electronic Health Record (EHR) systems. We describe how an implementation of such a RTS can be integrated in an EHR system using middleware technology based on web services. We describe the functional and technical requirements of such an approach and document our experiences with MedtuityEMR, an EHR system that stores patient data in XML.